RE-DESIGN SISTEM DISTRIBUSI AIR BERSIH DAN FIRE HYDRANT DI GEDUNG PLN UP3B KALSELTENG - Aji, Anas Satria; Siswanto, Rudi (JTAM ROTARY, 2021)
Sistem penyediaan dan distribusi air bersih di gedung-gedung bertingkat sering mengalami kendala. Tidak terkecuali PT. PLN (Persero) Gedung UP3B Kalselteng yang tidak luput dari permasalahan tersebut. Untuk itu perlu dilakukan perancangan ulang sistem distribusi dan penyediaan air bersih serta hidran kebakaran pada gedung. Tujuan dari penelitian ini antara lain menganalisis kebutuhan dan distribusi air bersih dan hidran kebakaran di dalam gedung. Kebutuhan air bersih dihitung berdasarkan jumlah penduduk yang mengkonsumsi air bersih, jenis dan jumlah unit beban alat perpipaan. Perhitungan head loss pada pipa menggunakan persamaan Hazen - William, Darcy-Weisbach dan Colebrook-White. Clean water supply and distribution systems in high-risk buildings often experience problems. No exception is the PT. PLN (Persero) UP3B Kalselteng Building which did not escape this problem. For this reason, it is necessary to re-design the distribution system and provide clean water and fire hydrants to the building. The objectives of this study include analyzing the needs and distribution of clean water and fire hydrants in the building. Clean water needs were calculated based on the number of people that consuming the clean water, the type and number of plumbing tools load unit. Calculation of head  loss  in  pipes  used Hazen – William, Darcy-Weisbach  and  Colebrook-White equation.Clean water supply and distribution systems in high rise buildings often experience problems. No exception is the PT. PLN (Persero) UP3B Kalselteng Building which did not escape this problem. For this reason, it is necessary to re-design the distribution system and provide clean water and fire hydrants to the building. The objectives of this study include analyzing the needs and distribution of clean water and fire hydrants in the building.Clean water needs was calculated based on the number of people that consuming the clean water, the type and number of plumbing tools load unit. Calculation of head  loss  in  pipes  used Hazen – William, Darcy-Weisbach  and  Colebrook-White equation.